Application of Kernel Density Estimates to Lead Isotope Compositions of Bronzes from Ningxia, North‐West China. - Hsu, Y.‐K.; Rawson, J.; Pollard, A. M.; Ma, Q.; Luo, F.; Yao, P.‐H.; Shen, C.‐C. (Archaeometry, 2018)
The aim of this paper is to apply kernel density estimates (KDEs) to the visualization and interpretation of lead isotope data from bronze assemblages found along the northern border of central China, here designated as the Arc. New lead isotope analyses of 30 leaded tin–bronze artefacts from the Wangdahu cemetery (c.500–300 bc) in the Ningxia Hui Autonomous Region, north‐west China, provide the basis for the discussion. By using multivariate KDEs and the calculated likelihood of the overlap, the present work shows that the Wangdahu objects feature a unique linear array of isotope ratios, representing an important element of overall bronzes from the Arc in the first millennium bc. This characteristic isotope signature is fundamentally different from that of Dajing ores in north‐east China, as well from that of early Qin bronzes in Shaanxi and Gansu provinces. This suggests that a variety of metal resources were utilized by peoples living in the Arc. The KDE approach thus proves effective at presenting and comparing lead isotope data.